2019
DOI: 10.9734/mrji/2019/v28i630150
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Susceptibility Analysis of Gram Negative Pathogens in Super Specialty Tertiary Care Centers, Pune in India from January 2018- January 2019

Abstract: Background and Objective: The encumbrance of antimicrobial resistance worldwide is substantive and likely to rise without any appropriate treatment which has enhanced the urge for the development of either new antibiotics or adjuvant therapy with antibiotics. Thus, we aimed to study a comparative antibiogram pattern of 758 clinical isolates collected from Pawana Hospital and Accord SDH, Pune (India), towards Elores (a novel antibiotic and adjutant entity of ceftriaxone, sulbactam and disodium edetate) and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…A similar study performed by Satras reported superior antibacterial activity of CSE (87.80%) as compared to carbapenem drugs (meropenem: 62.67% and imipenem: 60.95%) and was far better to piperacillin + tazobactam (48.42%) against 758 clinical pathogens. 24 Antibiogram profile depicted CSE as most susceptible drug toward both Enterobacteriaceae and non-Enterobacteriaceae isolates. 24 In our study, among, the “ESBL group”, CSE and colistin showed 100% sensitivity toward Acinetobacter .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study performed by Satras reported superior antibacterial activity of CSE (87.80%) as compared to carbapenem drugs (meropenem: 62.67% and imipenem: 60.95%) and was far better to piperacillin + tazobactam (48.42%) against 758 clinical pathogens. 24 Antibiogram profile depicted CSE as most susceptible drug toward both Enterobacteriaceae and non-Enterobacteriaceae isolates. 24 In our study, among, the “ESBL group”, CSE and colistin showed 100% sensitivity toward Acinetobacter .…”
Section: Discussionmentioning
confidence: 99%
“… 24 Antibiogram profile depicted CSE as most susceptible drug toward both Enterobacteriaceae and non-Enterobacteriaceae isolates. 24 In our study, among, the “ESBL group”, CSE and colistin showed 100% sensitivity toward Acinetobacter . “CSE” was much more effective toward Enterobacteriaceae (95%) as compared to colistin (89%).…”
Section: Discussionmentioning
confidence: 99%
“…while it was K. pneumoniae among the members of Enterobacteriaceae that showed high resistance. Indian studies on gram negative bacterial infections have reported high rates of resistance for β-lactams, β-lactamsβ-lactamase inhibitors and rapidly rising trend for carbapenems 19,20 . Irrational and overuse of the reserve antibiotics like carbapenems and colistin which are recommended only in MDR cases 21 has led to their increased resistance.…”
Section: Discussionmentioning
confidence: 99%